Genetic Characterization of Spondweni and Zika Viruses and Susceptibility of Geographically Distinct Strains of Aedes aegypti, Aedes albopictus and Culex quinquefasciatus (Diptera: Culicidae) to Spondweni Virus. - Andrew D Haddow; Farooq Nasar; Hilda Guzman; Alongkot Ponlawat; Richard G Jarman; Robert B Tesh; Scott C Weaver (PLoS Neglected Tropical Diseases)
Background Zika virus (ZIKV) has extended its known geographic distribution to the New World and is now responsible for severe clinical complications in a subset of patients. While substantial genetic and vector susceptibility data exist for ZIKV, less is known for the closest related flavivirus, Spondweni virus (SPONV). Both ZIKV and SPONV have been known to circulate in Africa since the mid-1900s, but neither has been genetically characterized by gene and compared in parallel. Furthermore, the susceptibility of peridomestic mosquito species incriminated or suspected in the transmission of ZIKV to SPONV was unknown. Methodology/principal findings In this study, two geographically distinct strains of SPONV were genetically characterized and compared to nine genetically and geographically distinct ZIKV strains. Additionally, the susceptibility of both SPONV strains was determined in three mosquito species. The open reading frame (ORF) of the SPONV 1952 Nigerian Chuku strain, exhibited a nucleotide and amino acid identity of 97.8% and 99.2%, respectively, when compared to the SPONV 1954 prototype South African SA Ar 94 strain. The ORF of the SPONV Chuku strain exhibited a nucleotide and amino acid identity that ranged from 68.3% to 69.0% and 74.6% to 75.0%, respectively, when compared to nine geographically and genetically distinct strains of ZIKV. The ORF of the nine African and Asian lineage ZIKV strains exhibited limited nucleotide divergence. Aedes aegypti, Ae. albopictus and Culex quinquefasciatus susceptibility and dissemination was low or non-existent following artificial infectious blood feeding of moderate doses of both SPONV strains. Conclusions/significance SPONV and ZIKV nucleotide and amino acid divergence coupled with differences in geographic distribution, ecology and vector species support previous reports that these viruses are separate species. Furthermore, the low degree of SPONV infection or dissemination in Ae. albopictus, Ae. aegypti and Cx. quinquefasciatus following exposure to two geographically and genetically distinct virus strains suggest a low potential for these species to serve as vectors.